下顎歯肉に生じた混合性結合組織亜系リン酸塩尿性間葉系腫瘍の1例 - 宮崎, 晃亘; 佐々木, 敬則; 金子, 剛; 出張, 裕也; 平塚, 博義; 五十嵐, 友彦 (日本口腔外科学会雑誌, 2012)
Tumor-induced osteomalacia （TIO） is a rare paraneoplastic syndrome that results in renal phosphate wasting with hypophosphatemia. Recently, it was reported that tumors associated with TIO produce fibroblast growth factor （FGF）-23, identified as the last member of the FGF family, and that excessive action of FGF-23 causes TIO. The tumor responsible for TIO is usually very small, and it is difficult to identify the location of the tumor; therefore, full body examination is required. Our patient was a 39-year-old man who presented with severe bone pain and muscle weakness of 4 years’ duration in the lower limbs. There was no family history of metabolic bone disease. The patient’s laboratory findings revealed hypophosphatemia due to renal phosphate wasting and an unusually high serum level of FGF-23. An abnormal mass was observed in the mandibular gingiva. After surgery, the serum levels of FGF-23 and phosphate rapidly normalized. The pathologic diagnosis of the tumor was phosphaturic mesenchymal tumor mixed connective tissue variant. Six months after the operation, the chronic bone pain affecting the entire body improved to a great extent, and the patient was able to walk without any support. We conclude that overproduction of FGF-23 by the phosphaturic mesenchymal tumor mixed connective tissue variant in the mandibular gingiva caused osteomalacia.